Preoperative anemia and associated factors in women undergoing cesarean section at a comprehensive specialized referral hospital in Ethiopia - Hassen, Alemayehu Eshetu; Agegnehu, Abatneh Feleke; Admass, Biruk Adie; Temesgen, Mamaru Mollalign (Frontiers in Medicine, 2023)
Background Anemia is a common public health burden during pregnancy. Severe maternal and fetal complications have been associated with anemia. Despite many studies on anemia during pregnancy have been conducted in Ethiopia at any time of antenatal care visits, the prevalence of preoperative anemia among women awaiting cesarean delivery and its contributing factors have not been determined. The aim of this study was to determine the prevalence and associated factors of preoperative anemia in women awaiting cesarean section at a comprehensive specialized hospital in Ethiopia. Methods An institution-based cross-sectional study was done from April to June 2022 to determine preoperative anemia in women undergoing cesarean delivery. Data were obtained using a standardized questionnaire that included the women’s background characteristics. Bi-variable and multi-variable logistic regression analyses were performed to identify variables related to preoperative anemia. With a 95% confidence level, the estimated crude odds ratio and adjusted odds ratio were calculated. In a multivariate analysis, variables were considered statistically significant if their p-value was less than 0.05. Results A total of 424 pregnant women with a 100% response rate were included in this study. The prevalence of preoperative anemia among women awaiting cesarean delivery was 28.3% (95% CI: 23.8–32.5%). Previous history of abortion, lack of iron supplementation, human immunodeficiency virus infection, previous cesarean section, and American Society of Anesthesiology class III were significantly associated with preoperative anemia among women awaiting cesarean section. Conclusion and recommendation Preoperative anemia was diagnosed in a significant proportion of women awaiting cesarean-delivery. Anemia was linked to a lack of iron supplementation, American Society of Anesthesiology class III, previous history of abortion, human immunodeficiency virus infection, and previous cesarean section. Therefore, early detection of high-risk pregnancies, iron supplementation, prevention of HIV infection and due attention to people living with HIV/AIDs are paramount.